High quality upconversion luminescence and excellent thermal stability of Yb3+, Er3+ codoped Sr3NaY(PO4)3F phosphors. (August 2021) - Wang, Shiping; Zhang, Bingye; Li, Ying; Zhang, Jinsu; Chen, Baojiu
Graphical abstract: High quality upconversion luminescence of Sr3 NaY(PO4 )3 : Yb 3+, Er 3+ phosphors and their excellent temperature stability. Highlights: The upconversion properties of the SNYPF: Yb 3+, Er 3+ under the 980 nm excitation are investigated. The intensity of green emission remains almost unchanged with the increasing of temperature. The red light region only contains two emission peaks from the thermally coupled stark levels. The maximum sensitivity of SNYPF: Yb 3+, Er 3+ are 0.00312 K −1 at 464 K and 0.00272 K −1 at 209 K for green and red emission. Abstract: A series of Sr3 NaY(PO4 )3 F (SNYPF): Yb 3+, Er 3+ phosphors were synthesized by high temperature solid-phase method. The green and red emission region of SNYPF: Yb 3+, Er 3+ in the upconversion luminescence (UCL) spectra consist of two distinctly separated peaks under 980 nm laser excitation, which can be assigned to the transition from 2 H11/2, 4 S3/2 and 4 F9/2 to 4 I15/2 of Er 3+ . The SNYPF: Yb 3+, Er 3+ phosphors possess significant optical temperature sensing feature with the maximum sensitivity value of 0.00312 K −1 (464 K) and 0.00272 K −1 (209 K), as well as 0.00242 K −1 and 0.00244 K −1 at 300 K for green and red emission, respectively. Notably, the intensity of green emission remains almost unchanged with the increasing of temperature, indicating the excellent thermal stability of the phosphors. The above results demonstrate that SNYPF: Yb 3+, Er 3+ is a potential UC phosphor, which is suitable for optical temperature sensing.